2021
DOI: 10.4103/mjhs.mjhs_31_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression, anxiety, and stress among medical students of one private medical college

Abstract: Background: Data show that the prevalence of depression, anxiety, and stress is more among medical students compared to general population and thus proving that the community of the medical students is a vulnerable group or high-risk group, where we need to take adequate measures to counter this issue among this particular community. Objective: The objective of the study was to study the prevalence of depression, anxiety, and stress among one of the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…17 In a study done by Vasugi et al reported moderate level of stress and no significant differences for level of stress and anxiety and depression based on demographic factors (marital, gender and age) as seen by present study. 18,9 In a study conducted by Chandan et al mentioned prevalence of stress was 91.67%, among them 37.50% had mild and 22.50% had severe level of stress which was found to be more than the present study. 19 In Malaysian study done by Yusuf et al, the prevalence of distressed postgraduate students was 36.4%.…”
Section: Grand Total 108contrasting
confidence: 44%
See 1 more Smart Citation
“…17 In a study done by Vasugi et al reported moderate level of stress and no significant differences for level of stress and anxiety and depression based on demographic factors (marital, gender and age) as seen by present study. 18,9 In a study conducted by Chandan et al mentioned prevalence of stress was 91.67%, among them 37.50% had mild and 22.50% had severe level of stress which was found to be more than the present study. 19 In Malaysian study done by Yusuf et al, the prevalence of distressed postgraduate students was 36.4%.…”
Section: Grand Total 108contrasting
confidence: 44%
“…7,8 Similar findings also found by Ameer RS and Ramya et al in their studies with moderate levels of stress among the study participants. 9,10 In a study done by Verma et al found most of the participants suffered from stress which were mostly related with somatic and cognitive symptoms. 11 By Shete et al also reported a high level of stress among postgraduate medical students.…”
Section: Grand Total 108mentioning
confidence: 99%
“…Similar results were shown by Seema et al [16] depicting higher odds in adolescents 16-19 years of age, male gender, higher socioeconomic status, having less physical activity and watching television > 2 hours/day. Also Ameer et al [25] reported higher odds in sex, father occupation, father literacy, socioeconomic status, and diet type.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, AlFaris et al found a high prevalence of depression among students of dentistry (51.6%), medicine (46.2%), applied medical sciences (45.7%), and nursing (44.2%), and was significantly higher among females [ 7 ]. Another local study screened medical students for anxiety and depression and found significant gender differences in the prevalence of anxiety and depression (females 66.6%, males 44.4%), and the rate was much higher in the first year (females 89.7%, males 60%) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%